A study on relationship among free cash flow, firm value and investors’ cautiousness: Evidence from Tehran Stock Exchange - Hassan Ghodrati; Abbas Hashemi (Management Science Letters)
Financial statements as well as financial standards are always considered as primary sources for getting rich information of firms. The standards are normally divided in two categories of economic and accounting and each of these standards shows one of the specifications of the company and has its own advantageous and disadvantageous. There are different standards, which are used for firm assessment. Therefore, a company with more gained prominences has more change to succeed in attracting credits and financing from the capital market. Under such circumstances, such a company can attract more finance and it can be sold sooner on the stock exchange. This paper tries to investigate on the free cash flow as an effective factor in specifying the real value of the business enterprises on 56 selected firms from Tehran Stock Exchange. The results of this study have disclosed that, there was a direct and meaningful relationship between free cash flow of the business enterprises and their real values. Second, the real values of the business enterprises are more than their predicted values. Finally, the predicted value of the business enterprises on the basis of the free cash flow is more than their market value.